Analisis Lagu Pantang Mundur Ciptaan Titiek Puspa - Fatma Gustia Ulfa; Jagar Lumbantoruan (SENDRATASIK UNP, 2020)
This study discusses the analysis of the Pantang Mundur song created by Titiek Puspa. It is related to the rhythm, melody, harmony, form, expression, and the relationship between the lyrics and melody. This research is a qualitative research. It uses a content analysis approach which is systematic, objectivity, and generalization. The research data were collected from library study activities and laboratory work. Based on the research, this song has a rhythmic basic motif which then undergoes development. The tone interval is dominated by Second Major (M2), and Prime Perfect (P1). In general, there are 10 motives found in the song. They are k, k1, lm, n, n1, n2, o, p, and q derived from 5 antecedent phrases namely A (3 times repetition), X, B and 3 consequent phrases X (2 times repetition), and Y. This song also consists of three forms, namely the forms A, A 'and B. The relationship between melody and lyrics in this song is predominantly syllabic even though there are several neural bars. This song is also categorized as Logogenic (prioritizing the text) which has two kadens: The Perfect Authentic Cadence and The Authentic Half Cadence. If the meaning contained in the lyrics of the song Pantang Mundur is associated with the melody journey of the song which is arranged in a step - step - jump - step - step - step - jump – etc, it gives the meaning that this song is a contemplation of a willingness, sincerity of soul, and the magnanimity of a wife to accept the departure of her husband who fought on the battlefield. In addition, some parts of the song are also composed of melodic character formulations which mean rigidity as well as melodies which leap to high intervals. This significantly means that it sparks the spirit of the warriors to achieve state majesty